Antibacterial Activity of Water Soluble and Fat- Soluble Vitamins against Drug Resistance Clinical Bacteria Klebsiella Pneumonia - Kader, Afrah Abdul; Azeez, Alfiya; Mahjabin, Ayifa; Babu, Fairos; Mikacha, Farha Madathil; Shabeena, Fathima; Fathima, Fida; Sulthana, Fidha; Hanna, Hameena; Parambatt, Hanoona; Peediyakkal, Jumni Ambalavan Puthan; Shihab, Lafa; et al. (Asian Journal of Biological and Life Sciences)
Background: Vitamins play an important role in enhancing immunity, which helps the body fight various infections. Aim: This study investigates the antimicrobial activity of Biotin (Vitamin B7) and Ascorbic Acid (Vitamin C) against clinically significant microorganisms, specifically Klebsiella pneumoniae. We explored their potential as agents for disrupting protein biotinylation and the mechanisms underlying their antimicrobial effects. Materials and Methods: Clinical microorganisms were obtained from the Clinical Microbiology Lab in Coimbatore, India and cultured to match the MacFarland standard turbidity. The Kirby-Bauer Method was used to assess the antimicrobial activities of Biotin, Ascorbic Acid, and other vitamins against K. pneumoniae. The Minimum Inhibitory Concentrations (MIC) of Biotin and Ascorbic Acid were determined using a serial dilution method. Transmission Electronic Microscopy (HR-TEM) was used to visualise the antimicrobial effects of Biotin and Ascorbic Acid on K. pneumoniae. Results: The results showed antimicrobial activity of Biotin and Ascorbic Acid against K. pneumoniae, with zones of inhibition of 14 and 12 mm, respectively. The MIC values for Biotin and Ascorbic Acid were 62.5 and 125 μg/mL, respectively. HR-TEM analysis revealed significant morphological alterations in the treated bacterial cells compared with those in untreated cells. Conclusion: This study provides insights into the antimicrobial potential of Biotin and Ascorbic Acid, and highlights their mechanisms of action. Unlike traditional antibiotics, these vitamins demonstrate promising antimicrobial effects and have potential applications as combination therapies or adjuncts to conventional treatments.
Keywords: Anti-microbial activity; Anti-microbial resistance; Ascorbic acid (C); Biotin (B7); MIC